A 400nW single-inductor dual-input-tri-output DC-DC buck-boost converter with maximum power point tracking for indoor photovoltaic energy harvesting - Chew, Kin Wai Roy (2013)
Energy harvesting enables the remote sensors of the wireless sensor network to obtain power from the environment for their entire lifetime. For indoor remote sensors, amorphous silicon photovoltaic (PV) cell can be used to harvest energy from indoor lighting. Furthermore, if the power consumption of the sensor is low, e.g., the image sensor in [1], the power rating of the PV cell can be limited to tens or hundreds of microwatts to minimize the form factor of the sensor. However, as the output power of the PV cell varies greatly with illumination level [2] and the output voltage of the PV cell (VPV), an energy storage device, such as a battery, is required to regulate the harvester's output power. Furthermore, a DC-DC converter with a maximum power point tracker (MPPT) is needed to lock the PV cell at its maximum power point (MPP).